2014
DOI: 10.1007/s00296-014-3093-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteoarthritis in former elite athletes: a systematic overview of the recent literature

Abstract: The aim of this study was to systematically review the recent scientific literature to explore the prevalence of osteoarthritis (OA) in former elite athletes from team and individual sports. A systematic review of observational studies was conducted. Based on three categories of keywords (and synonyms), a sensitive search strategy was built in order to search MEDLINE and SPORTDiscus from 2000 to 2014. The data from included studies presenting a prevalence rate of OA as an outcome measure were extracted using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 55 publications
0
55
0
2
Order By: Relevance
“…This is difficult to assess because of the confounding factor of higher rates of traumatic joint injury in athletes owing to their sports participation, as well as great heterogeneity between studies related to this topic [123, 124]. Two mechanisms may predispose athletes to increased risk: firstly, increased high-impact joint loading as described for heavy manual workers; secondly, increased prevalence of cam morphology which may be caused by high levels of physical activity during a critical period during adolescence while osseous development is still occurring [125].…”
Section: Etiology and Risk Factors For Hip Oamentioning
confidence: 99%
“…This is difficult to assess because of the confounding factor of higher rates of traumatic joint injury in athletes owing to their sports participation, as well as great heterogeneity between studies related to this topic [123, 124]. Two mechanisms may predispose athletes to increased risk: firstly, increased high-impact joint loading as described for heavy manual workers; secondly, increased prevalence of cam morphology which may be caused by high levels of physical activity during a critical period during adolescence while osseous development is still occurring [125].…”
Section: Etiology and Risk Factors For Hip Oamentioning
confidence: 99%
“…While several risk factors have been identified, the causes of knee osteoarthritis are not well established. Age, obesity, and being overweight (body mass index, > 26), work-related activities, playing sports at high levels, and malalignment of the knee joint are the most prominent risk factors [1], [2], [3], [4]. There is probably also a genetic component and evidence suggests sex as a possible risk factor, with studies reporting higher prevalence of knee osteoarthritis in women over the age of 45 years [1].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically shoulder joints, for example, seldom seem to be affected in modern young individuals [87]. However, shoulder osteoarthritis has more often been reported among young elite athletes (particularly professional tennis players), suggesting that the repetitive strains introduced by certain exercises at a young age can cause micro-trauma in the cartilage [17]. Previous bioarchaeological studies also suggest that the high prevalence of shoulder osteoarthritis in male hunter-gatherers and agriculturalists is associated with excessive use of the joint during their daily activities [26,74,75,88].…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical and osteoarchaeological studies demonstrate that osteoarthritis can be caused by many factors such as age, sex, genetics, hormones, nutrition, systemic inflammation, and body mass among others [812]. It is well-established that intensive physical demands and mechanical strains can prompt the development of osteoarthritis [13–17]. Some studies have also shown that an etiological relationship can be determined between certain osteoarthritis patterns and specific occupational or habitual practices [1821].…”
Section: Introductionmentioning
confidence: 99%